A gentle occupation : a novel - Bogarde, Dirk
In the uneasy aftermath of WWII, a group of ordinary British soldiers and their families find themselves stationed as peacekeepers at an outpost in the Java Sea. Whilst attempting to return the island to Dutch control, they are subject to violent attacks by the locals who want their freedom. As the Empire crumbles, the island is plunged into chaos and violence amidst a nationalist uprising. Selfishness, sex, greed, fear and revenge, all play their part; though so too do the finer instincts of love, loyalty and concern. At times gloriously funny, never sitting in judgement, Dirk Bogarde portrays mankind's fallible, complex humanity as the thin skin of conventional behavior, tautened in the corrosive atmosphere of Southeast Asia, gradually begins to split. [By publisher]